Application of electrocardiogram knowledge in emergency care (心电图知识在急诊护理工作中的应用现状) - GENG Shenghua (耿胜华); PENG Wei (彭伟); LIU Xinrui (刘馨蕊); XIE Mengdi (谢梦迪); DONG Yanting (董燕婷); GAO Qianqian (高倩倩); ZHANG Qingcheng (张清晨) (中西医结合护理)
This paper reviewed studies on application of electrocardiogram knowledge in previewing triage, location of PICC tip and critical care of patients in the emergency department, and provided reference for improving awareness regarding electrocardiogram knowledge and technology among emergency nurses. (本文对心电图知识在急诊护士预检分诊、经外周静脉置入中心静脉导管(PICC)置管尖端定位以及急危重症护理等方面的研究现状进行综述, 从而为推动心电图知识在急诊护士中的应用提供一定的参考。)